Menemukan kembali esensi perpustakaan dalam relevansi dan transformasi literasi di era digital - Tazkia Mega Aulya (FPPTI Jawa Tengah, 2026)
The digital revolution has given rise to a literacy paradox in Indonesia. Amidst the current abundance of information access, there is no corresponding improvement in the quality of the public's digital comprehension. This situation demands a strategic transformation of libraries to remain relevant and functional in the modern era. This study aims to identify and analyze library transformation strategies that can be adopted to address this literacy gap. Using a qualitative method through a comprehensive literature review, this study analyzes various academic findings and current practices. The conclusion of this research reveals that an effective strategic library transformation must be built upon three pillars, where librarians must evolve from collection managers into Digital Literacy Guides, User Experience Architects, and Community Problem-Solving Partners who actively educate the public to navigate, evaluate, and utilize digital information critically and ethically. The integration of these three pillars is directed at addressing the root cause of the literacy paradox: by positioning libraries as knowledge curators and adaptive community innovation hubs. The application of this model is expected to optimize the role of libraries as adaptive and inclusive knowledge curators and community innovation centers within society. Thus, this transformation represents a fundamental repositioning of libraries from mere access providers into institutions that actively build societal literacy resilience. Consequently, libraries become a solid and dynamic foundation of knowledge amidst the increasingly rapid flow of digital information.